Farmers' Perception of Leopard (Panthera Pardus) Conservation in a Human Dominated Landscape in Northern Ethiopian Highlands - Yirga, Gidey; Bauer, Hans (Richtmann Publishing, 2011)
Attitudes toward large carnivores were surveyed in two sub districts May Anbesa (relatively high leopard density are)and Egriwonber (area with no leopard) in the northern Ethiopian highlands. This district is a completely human dominatedlandscape, where conflict has manifested in terms of livestock depredation. Spotted hyena (Crocuta crocuta), leopard (Pantherapardus) and common jackal (Canis aureus aureus) are common in this landscape but all other large carnivores are virtuallyabsent. A structured survey instruction was prepared in the form of an interview-based questionnaire containing 23 itemsarranged in three sections: attitudes and perceptions; management issues; and economic impact. We interviewed 519 randomlyselected households (core area, n=317 and control area, n=202). Majority of the respondents (64.6%) had positive feelings andonly 10.2% had negative feelings in the core area, whereas majority of the respondents (52.3%) had neutral feelings and only9.1% negative feelings towards leopard in the control area. The mean attitude score in both areas was 3.53: neutral to positive.The majority of respondents (72.3%), including 88.6% in the core area and 46.5% in the control area, thought that compensationshould be paid to farmers whose livestock had been killed by leopards. Only 34.7% of all participants, including 25.9% in thecore area and 48.5% in the control area, agreed that killing of leopards should be strictly regulated. Farmers of the core areareported losses of 85 domestic animals due to leopard depredation causing an estimated financial loss of about US 51,673over the last five years, or an annual mean of 0.4% of stock worth US 10,334. Of all the respondents in core area only 12% ofthe people had suffered from leopard depredation. Goats were the most depredated livestock species (49.4%). The findingsindicate that tolerance for depredation is high for that further efforts could improve support for carnivore conservation.